Prevalence and determinants of socioeconomic inequality in caesarean section deliveries in Bangladesh: an analysis of cross-sectional data from Bangladesh Demographic Health Survey, 2017-18 - Pradeep Kumar; Himani Sharma (BMC, 2023)
Abstract Background Caesarean section deliveries, which involve incisions in the abdomen and uterus of the mother, have been a widespread event among women with obstructed labour. The current study not only estimated the socioeconomic and demographic factors of caesarean deliveries in Bangladesh but also decomposed the existing socioeconomic inequality in caesarean deliveries. Data and methods 2017-18 Bangladesh Demographic and Health Survey (BDHS) data was used for this study. The adequate sample size for the analysis was 5,338 women aged 15-49 years who had given birth at a health facility for three years preceding the survey. Explanatory variables included women's age, women's educational level, women's working status, mass media exposure, body mass index (BMI), birth order, Ante Natal Care (ANC) visits, place of delivery, partner's education and occupation, religion, wealth index, place of residence, and divisions. Descriptive statistics along with bivariate and multivariate logistic regression analysis was performed to identify the factors associated with the outcome variable. Concentration index and concentration curve were made to measure the socioeconomic inequality in caesarean births in Bangladesh. Further, Wagstaff decomposition analysis was used to decompose the inequalities in the study. Results About one-third of the deliveries in Bangladesh were caesarean. Education of the women and the family's wealth had a positive relationship with caesarean delivery. The likelihood of caesarean delivery was 33% less among working women than those who were not working [AOR: 0.77; CI: 0.62-0.97]. Women who had mass media exposure [AOR: 1.27; CI: 0.97-1.65], overweight/obese [AOR: 1.43; CI: 1.11-1.84], first birth order, received four or more Antenatal check-ups (ANC) [AOR: 2.39; CI: 1.12-5.1], and delivered in a private health facility [AOR: 6.69; CI: 5.38-8.31] had significantly higher likelihood of caesarean delivery compared to their counterparts. About 65% of inequality was explained by place of delivery followed by wealth status of the household (about 13%). ANC visits explained about 5% of the inequality. Furthermore, the BMI status of the women had a significant contribution to caesarean births-related inequality (4%). Conclusion Socioeconomic inequality prevails in the caesarean deliveries in Bangladesh. The place of delivery, household wealth status, ANC visits, body mass index, women's education and mass media have been the highest contributors to the inequality. The study, through its findings, suggests that the health authorities should intervene, formulate specialized programs and spread awareness about the ill effects of caesarean deliveries amongst the most vulnerable groups of women in Bangladesh.